2013
DOI: 10.1007/s13760-013-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis: relationship with disease duration, physical disability, disease pattern, age and sex

Abstract: To evaluate the relationship between disease duration, disability, disease pattern, age and sex with fatigue in MS patients. One hundred and seventy-three clinically definite MS patients and 87 age-matched healthy controls enrolled in this cross sectional study. Demographic data (sex, age), duration of the disease and disease pattern extracted from patient's files and Kurtzke Expanded Disability Status Scale (EDSS) were recorded for each patient by an expert neurologist. Participants were asked to answer the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
5
38
2
1
Order By: Relevance
“…Fatigue is a universal experience in both normal and clinical populations and a common symptom of multiple diseases (Carter et al, 1993; Bonner et al, 2013; Fabbrini et al, 2013; Ghajarzadeh et al, 2013). Recent studies have identified DMN dysfunction in some clinical populations in which fatigue symptoms are pervasive.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a universal experience in both normal and clinical populations and a common symptom of multiple diseases (Carter et al, 1993; Bonner et al, 2013; Fabbrini et al, 2013; Ghajarzadeh et al, 2013). Recent studies have identified DMN dysfunction in some clinical populations in which fatigue symptoms are pervasive.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue in MS has previously been linked to age, disability, MS type, and sex (28, 29), with some suggestion that disability is a driving factor (30). For this reason, data were extracted from articles to consider disability, measured using the extended disability status scale (EDSS)(31), and MS type as moderators (age and sex could not be included due to insufficient reporting in the articles).…”
Section: Methodsmentioning
confidence: 99%
“…Fatigue in MS is neither consistently linked to disease severity as measured by the Expanded Disability Status Scale (EDSS 5 ) nor disease duration, although it is generally found to be worse in individuals with the secondary progressive subtype. 2,6 Fatigue is distinct from sleepiness, and fails to improve with adequate sleep. 7 Multiple factors are thought to contribute to fatigue 8,9 with no specific biomarker or etiology yet confirmed.…”
Section: Introductionmentioning
confidence: 99%